2004
DOI: 10.1097/00002508-200411000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Pain Reduction in Chronic Back and Neck Pain After Multimodal Treatment

Abstract: Patients who reported unchanged or increased pain after multimodal treatment could be predicted with good accuracy, whereas those who reported decreased pain were more difficult to identify. Treatment-related pain alteration in chronic low back pain seems to be predicted by partly different variables than in chronic neck pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 37 publications
2
42
0
3
Order By: Relevance
“…According to the biopsychosocial model, catastrophizing is a central variable in the fear-avoidance cycle, leading to chronic pain-related disability [38]. Thus, addressing the cognitive distortions occurring in catastrophizing, for instance by an evidence-based cognitive behavioral approach, may interrupt the fear-avoidance cycle and help to reduce the pain chronicity and disability [39].The possible implications to health policy makers may involve considering the long-term cost-effectiveness of a more expensive and articulated multi-modal approach, including cognitive-behavioral therapy, dedicated to patients with chronic neck pain with baseline catastrophic thinking [8,40].…”
Section: Predictors Of Poor Outcomementioning
confidence: 99%
“…According to the biopsychosocial model, catastrophizing is a central variable in the fear-avoidance cycle, leading to chronic pain-related disability [38]. Thus, addressing the cognitive distortions occurring in catastrophizing, for instance by an evidence-based cognitive behavioral approach, may interrupt the fear-avoidance cycle and help to reduce the pain chronicity and disability [39].The possible implications to health policy makers may involve considering the long-term cost-effectiveness of a more expensive and articulated multi-modal approach, including cognitive-behavioral therapy, dedicated to patients with chronic neck pain with baseline catastrophic thinking [8,40].…”
Section: Predictors Of Poor Outcomementioning
confidence: 99%
“…We accepted 5 studies which examined gender as a prognostic factor. [19][20][21][22]26 Two phase I studies looking at general population samples found a modest effect of gender, in that men were 33% 21 and 47% 22 more likely than women to have complete resolution of neck pain over a 1-year and 5-year follow-up period, respectively. The former study also reported that women were 19% more likely than men to have persistent pain.…”
Section: Demographic and Socioeconomic Factorsmentioning
confidence: 99%
“…Insofern wurde auf eine Diagnosen differenzierende Auswertung verzichtet. Es scheint aber Hinweise auf Unterschiede zu geben [20].…”
Section: Tab 4 Ergebnisse Der Linearen Regression Zurunclassified